Corrosion of dental amalgams: electrochemical study of Ag-Hg, Ag-Sn and Sn-Hg phases - Acciari, H. A.; Guastaldi, Antonio Carlos [UNESP]; Brett, CMA (Elsevier B.V., 2001)
Dental amalgams, formed by reaction of mercury with a powder alloy containing mainly Ag, Sn, Cu and Zn, have a complex metallurgical structure which can contain up to six phases. Their observed corrosion is thus a complex process, which involves contributions from each of the phases present as well as intergranular corrosion. It is thus of interest to investigate the corrosion of individual phases present in dental amalgams. In this work the corrosion behaviour in 0.9% NaCl solution of Ag-Hg, Ag-Sn and Sn-Hg phase components of dental amalgams was investigated by electrochemical methods. The corrosion resistance was found to decrease in the order gamma (1)-Ag2\Hg3, gamma -Ag3Sn and gamma (2)-Sn7Hg. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: dental amalgams; amalgam phases; corrosion; electrochemical impedance